Features of social adaptation of ethnic migrants (repatriates) to the social and cultural environment as a new marginal group in the structure of kazakh society (The Journal of Psychology and Sociology, 2017)
Relevance of the research problem is determined by the fact that the repatria-tion of ethnic Kazakhs to their historical homeland greatly affect the demographic structure and social structure of Kazakh society. The process of social adaptation of ethnic immigrants proceeds differently. The degree of social adaptation process depends, first of all, the motives, the reasons for the exodus from the country, the degree of relationship with the local people in the places of settlement and the desires of the immigrant. After returning to a new location, difficult to adapt to the external and internal conditions of social reality, which leads to drastic changes in lifestyle that have occurred to them after their repatriation, as well as experienced by the material, cultural, psychological, occupational difficulties. All this requires a focused study of the process of social adaptation of ethnic immigrants to modern Kazakhstani society in terms of an integrated approach.The object of the research is ethnic immigrants as a new marginal group of Kazakh society structures and identify the level of indicators for measuring suc-cess and entry into a new socio-cultural environment, the subject – the adaptation of ethnic immigrants. The level of social adaptation was measured by parameters such as assessment of the economic situation of the family, the assessment of the material situation, relations with the local population. Accordingly, there is a need to review all stages of the return of ethnic immigrants to their historic homeland, the step of forming motives, returnees process of adaptation to the new location as well as the process of self-identification in Kazakhstan society. Sociological research methods in the study of the causes of repatriation of compatriots will understand the underlying motives and factors affecting the desire to immigrate. Accounting for the motivational structure of the return of ethnic Kazakhs to their historical homeland increases the number of potential immigrants to immigrate to Kazakhstan.
Keywords: repatriates; social adaptation; migrants.